Notas sobre la ética de Husserl a Habermas (2012)
Throughout this paper we will show the direction of Edmund Husserl s phenomenological ethics as a renewal of man and culture; its limits and the ability to be complemented with the discourse ethics by Jürgen Habermas. We will highlight the approach that these authors have with their critical reflection on contemporary society and highlight the sense in that they understand the crisis of culture; not as something temporary and contingent; but as essential to culture itself. Thus; we will proceed to point out how to pass from an ethics-centered consciousness; to ethical standards based on communicative action on the merits of the world of life intersubjectively shared. In this perspective ethics may not appear depending on it for longer apologetic and transcendental philosophy justification as a science; a reflection of that rationality seeking some autonomy and freedom for the individual and the community as if it were of a universal science and essential to mancentered reason. This leads us to think in terms of communicative ethics; that is; to put consideration of all affected our principles and values in a speech community in which it seeks not knowledge and truth of things; but our understanding; normative rightness and understanding; based on our particular forms of life; our special worlds made of the various speech acts.